A MODIFIED SURGICAL SEPSIS MODEL SATISFYING SEPSIS-3 AND HAVING HIGH CONSISTENCY OF MORTALITY. Issue 4 (24th April 2023) - Wang, Jiebo; Liao, Lianming; Chen, Ying; Chen, Liji; Lai, Zhongmeng; Zhang, Liangcheng
ABSTRACT: Background : Cecal ligation and perforation (CLP) is currently considered the criterion standard model of sepsis; however, there are some deficiencies, such as low clinical relevance, inconsistency in severity grading, and an unknown proportion of CLP animals meeting the requirements of sepsis-3. Methods : Adult rats were randomly divided into the following three groups: modified CLP (M-CLP) group, CLP group, and sham group. The vital organ function of rats was evaluated 24 hours postoperatively by blood pressure, behavioral testing, histopathology, and blood test. Cytokine levels were determined by enzyme-linked immunosorbent assay, and T-cell suppression was assessed by flow cytometry. The stability of the model was evaluated by comparing the survival rates of repeated experiments in all groups from day 1 to day 14. Results : More rats in the M-CLP group met Sepsis-3 criteria than those in the CLP group 24 hours postoperatively (53.1% vs. 21.9%, P = 0.01). Rats in the M-CLP group developed more serious hepatic, pulmonary, and renal dysfunction. Similar to human sepsis, rats in the M-CLP group demonstrated more serious immunosuppression and systemic inflammation compared with the CLP group. In addition, disease development and severity, which was indicated by the stable survival rates of model animals, were more stable in the M-CLP group. Conclusions : More rats could meet Sepsis-3 criteria with this novel surgical procedure, which may reduce the number of animals needed in preclinical sepsis experiments. This stable M-CLP model may contribute to the development of new therapies.